2013
DOI: 10.1681/asn.2013040340
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Direct Priming of CD8 T Cells by Donor-Derived Cytomegalovirus Following Kidney Transplantation

Abstract: Cytomegalovirus (CMV) infection increases the risk of complications after renal transplantation, but the mechanisms controlling donor-derived infection are not adequately characterized. Here, we assessed the risk of clinically significant CMV disease in donor-seropositive, recipient-seropositive (D+R+) renal transplantation and examined recipients' CMV antigen-specific cellular immune responses primed directly by donor cells. In a retrospective cohort of 569 patients administered standardized basiliximab-tacro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Both the CD8 + and CD4 + T‐cell compartments are crucial for controlling and restricting viral replication . Nevertheless, while it is suggested the preponderant role of CD8 + T cells for the control of hCMV replication , it appears that CD4 + T cells would be fundamental for conferring long‐lasting protection , either through the provision of T‐cell help in maintaining virus‐specific antibody responses and expanding the CD8 + T‐cell populations or by directly killing virus‐infected cells . A highly diverse virus‐specific T‐cell response develops between 4 and 6 weeks after primary antigen exposure.…”
Section: Immune‐biology Against Hcmv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the CD8 + and CD4 + T‐cell compartments are crucial for controlling and restricting viral replication . Nevertheless, while it is suggested the preponderant role of CD8 + T cells for the control of hCMV replication , it appears that CD4 + T cells would be fundamental for conferring long‐lasting protection , either through the provision of T‐cell help in maintaining virus‐specific antibody responses and expanding the CD8 + T‐cell populations or by directly killing virus‐infected cells . A highly diverse virus‐specific T‐cell response develops between 4 and 6 weeks after primary antigen exposure.…”
Section: Immune‐biology Against Hcmv Infectionmentioning
confidence: 99%
“…To note, prediction of hCMV replication using different in vitro assays might potentially be misleading, especially among R+/D+, as hCMV peptides used as stimulators are presented by recipient HLA, thus in vivo viral presentation through donor cells could be underestimated .…”
Section: Clinical Scenarios For Monitoring Hcmv‐specific Cellular Immmentioning
confidence: 99%
“…These observations suggest a crucial role played by major histocompatability complex‐based viral recognition as uCB HCT often can allow greater degrees of HLA mismatching. Inadequate HLA matching likely results in poor presentation of viral epitopes to BKV‐specific CD8 + cytotoxic T cells and decreased viral clearance, as is demonstrated by cytomegalovirus infection in kidney transplantation patients . Furthermore, in kidney transplantation patients, greater degrees of HLA mismatching have been associated with increased incidences of BKV‐associated nephropathy .…”
Section: How Does Bkv Cause Disease After Hct?mentioning
confidence: 99%
“…We previously reported donor CMV positivity as a risk factor of graft loss, especially in CMV-infected recipients (D+R+). 8 Also, CMV is commonly detected in transplanted kidneys from CMV-positive donors 9,10 and replication of CMV within kidney grafts is associated with a poor clinical outcome. 9,11 In addition, we showed that the deleterious effect of donor CMV positivity on kidney graft outcome was mainly observed in kidney transplant recipients with full HLA-I mismatch with their donors or with a strong post-transplant reduction in CD8 + T cell number.…”
Section: Introductionmentioning
confidence: 99%